The Synoptic Characteristics, Causes, and Mechanisms of Kahlaa Tornado in Iraq on 14th April 2016 - Thaer O. Roomi; Firas S. Basheer (مجلة بغداد للعلوم)
In this study, an analysis of the synoptic characteristics, causes and mechanisms of Kahlaa tornado event was carried out. This tornado occurred on 10:30 UTC (1:30 pm Iraq Local Time) on 14 April 2016 to the north of Kahlaa town in Maysan governorate. We analyzed surface and upper charts, weather conditions, the damage indices, the dynamical features and the instability of the tornado. The analysis showed that there was a low pressure system which was an extension of the Monsoon low in addition to a supercell thunderstorm and a jet stream aloft. The cold trough and high relative vorticity at 500 hPa level, the humid warm wind blowing from the south and the dry cold wind from the north contributed to the initiation of the tornado. According to the damage amount, Kahlaa tornado can be classified as EF2 degree (considerable) on Enhanced Fujita scale. Three indices were calculated to estimate the instability of the tornado. The values of the convective available potential energy (CAPE), K-index, and lifted index were (≥2500 J/kg), (35.3 oC), and (-7), respectively. All these indices confirmed the instability required to form severe thunderstorm essential to tornado formation. Although the forecasting of tornadoes occurrence is difficult, there would be indications that may lead to expect of occurrence. These may include the availability of moisture, heat, and significant wind direction changes with altitude. However, the vital factors were the existence of high instability and a supercell thunderstorm.